Disrupting tRNA modifications to target mitochondrial vulnerabilities in drug-resistant leukemia cells - Pauli, Cornelius; Kienhöfer, Michael; Blank, Maximilian Felix; Begik, Oguzhan; Rohde, Christian; Zimmermann, Sarah; Werner, Laura; Heid, Daniel; Xu, Fu; Weidenauer, Katharina; Delaunay, Sylvain; Krall, Nadja; et al. (Blood, 2025)
Dysregulated RNA modifications contribute to cancer progression and therapy resistance, yet the underlying mechanism often remains unknown. Here, we perform CRISPR-based synthetic lethality screens to systematically explore the role of RNA modifications in mediating resistance to antileukemic drugs. We identify the tRNA methyltransferase 5 (TRMT5)-mediated formation of N1-methylguanosine (m1G) in the transfer RNA (tRNA) anticodon loop as essential for mediating drug tolerance to cytarabine and venetoclax (Ven) in acute myeloid leukemia (AML). TRMT5 methylates nearly all mitochondrial and nuclear tRNAs with a guanosine at position 37, but its role in promoting drug tolerance specifically depends on its mitochondrial function. TRMT5 is essential for the dynamic upregulation of mitochondrial messenger RNA translation and oxidative phosphorylation, which are critical for sustaining drug tolerance in leukemia cells. This mitochondrial dependency correlates with therapy outcomes in patients with leukemia: lower expression of electron transport chain genes is linked to poorer outcomes in a cohort of nearly 100 patients with AML undergoing first induction therapy. Finally, we demonstrate that targeted depletion of the TRMT5 protein using a conditional degron, in conjunction with cytarabine and Ven treatment, synergistically induces cell death in drug-tolerant AML cells. Thus, our study reveals TRMT5 as a promising drug target for therapy-resistant leukemia.
Gesehen am 29.01.2026